2019
DOI: 10.3168/jds.2018-15221
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography and behavioral biometrics associated with estrus indicators and ovulation in estrus-synchronized dairy cows housed in tiestalls

Abstract: Most Canadian dairy herds operate in tiestall housing (61%), where average estrus detection rates may be lower than 54%. The objective of this study was to evaluate infrared thermography and behavioral biometrics as indicators of estrus in dairy cows. Eighteen cyclic multiparous cows (Synch) were subjected to an estrus synchronization protocol, and 18 pregnant cows (control) received a sham protocol on the same schedule and frequency as the cyclic cow treatment. A decline in plasma concentrations of progestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Results showed that the temperature of the perineal region ( regio perinealis ), especially the vulvar area, the orbital region ( region orbitalis ), including the eye, facial regions ( regiones faciei ) such as the cheek, neck regions ( regiones colli ), the wither region ( regio interscapularis ), the flank region ( regio abdominis lateralis ), and the rump region ( r egio glutea ) all increased by approximately 1.2 °C and remained in that range for 24 and 48 h before ovulation, compared to the day of ovulation and four days before it. These data reveal the relation between temperature variability in this region and estrus in cattle [ 51 ].…”
Section: Perineal Region ( Regio Perinealis )mentioning
confidence: 97%
See 1 more Smart Citation
“…Results showed that the temperature of the perineal region ( regio perinealis ), especially the vulvar area, the orbital region ( region orbitalis ), including the eye, facial regions ( regiones faciei ) such as the cheek, neck regions ( regiones colli ), the wither region ( regio interscapularis ), the flank region ( regio abdominis lateralis ), and the rump region ( r egio glutea ) all increased by approximately 1.2 °C and remained in that range for 24 and 48 h before ovulation, compared to the day of ovulation and four days before it. These data reveal the relation between temperature variability in this region and estrus in cattle [ 51 ].…”
Section: Perineal Region ( Regio Perinealis )mentioning
confidence: 97%
“…This peripheral vascular and nervous network is known to respond to stressful or harmful stimuli. It is represented in Figure 3 , showing the location of the orbital region in the medial canthus of the eyelids [ 30 , 49 , 50 , 51 ]. These fibers are sensitive to neurosecretion of epinephrine and norepinephrine that promotes vasoconstriction in the capillaries, thus reducing heat exchange rate and functioning as a local thermoregulating mechanism [ 14 ].…”
Section: Orbital Region ( Regio Orbitalis )mentioning
confidence: 99%
“…The amygdala, NAc and BDNST also have a role in the reward system and maternal memory, and the former in the olfactory recognition of the offspring. ADH: antidiuretic hormone; BNST: bed nucleus of the stria terminalis; MPOA/AH: medial preoptic area/anterior hypothalamus; NAc: nucleus accumbens; OX: oxytocin; PRL: prolactin; PVN: paraventricular nucleus; VTA: ventral tegmental area, adepted from [ 110 , 111 , 112 , 113 , 114 ].…”
Section: Figurementioning
confidence: 99%
“…Thermal cameras first started to be used in military areas and later became widespread in industrial areas (Polat et al 2010). Recently, IRT has been used frequently for early diagnosis of some diseases such as mastitis (Bitman et al 1984;Porcıonata et al 2009;Polat et al 2010;Sathiyabarayhi et al 2016and Golzarian et al 2017), lameness (Eddy et al 2001Alsaaod et al 2012;Stokes et al 2012;Gianesella et al 2018;Fabbri et al 2020), östrus detection (Hurnik et al 1985;Talukder et al 2014;Marquez et al 2019), sperm quality (Menegassi at al. 2015), pregnancy (Jones at al.…”
Section: Intrоduсtiоnmentioning
confidence: 99%